Surface Studies of Oxidised Metals: Mo, Nb and Cu - Walshe, Killian (Trinity College Dublin. School of Physics. Discipline of Physics, 2021)
The atomic structure and evolution of ultra-thin film oxides is investigated for Mo, Nb and Cu using surface sensitive techniques such as scanning tunneling microscopy (STM), scanning tunneling spectroscopy (STS), low energy electron diffraction (LEED) and x-ray photoelectron spectroscopy (XPS). In particular, the structural and electronic properties of the oxide layer and the way in which the oxide layer governed further oxidation through its barrier to oxygen incorporation is investigated. An O-Mo-O tri-layer oxide structure terminates (MoO2/Mo(110)). Over-oxidising MoO2/Mo(110) MoO2/Mo(110) results in an oxygen-rich MoO2+x$/Mo(110) termination. The extra oxygen takes the form of adatoms, which reside on the row structure of MoO2/Mo(110). Applying a bias pulse between the STM tip and the surface, results in the removal of oxygen adatoms from the surface. The electric field produced between the STM tip and the surface is concluded to ``push'' the adatom into the surface through the terminating layer: Finite element method (FEM) simulations using an electric field support the experimental results and indicate that an electric potential of 0.45V is required for the adatom for it to overcome the barrier. An intermediate state for the oxygen adatoms is observed, partially contained within the oxide layer. Adatom removal is only observed with positive sample bias. The oxygen adatom is removed from the surface via penetration through the surface oxide layer. Density functional theory (DFT) calculations indicate that the oxygen adatom opens a ``channel'' in the oxide layer, by relaxing a neighbouring Mo atom from its lattice position into the topmost oxygen layer. This relaxation reduces the potential barrier and allows for oxygen incorporation with relative ease compared to the unrelaxed case. The size of region on the surface from which adatoms are removed depends on the magnitude of applied voltage pulse. The highest resolution of the pulsing mechanism is on the sub-nanometer scale. An ultra-thin NbO layer terminates Nb(110). This oxide layer produces a surface with two terrace structures, one of which has terrace edges in the [001] direction and the other exhibits terrace edges in both the Nb[001] and [-111] directions. STS measurements indicate a difference in the local density of states (LDoS) between the nanocrystals which terminate the surface and the ``channel'' separating neighbouring nanocrystals. The two types of terrace edges Nb[001] and [-111] are electronically distinct from one another. The terraces edges which runs in the Nb[001] direction regularly exhibit a terrace width of one NbO nanocrystal. Low dosage oxygen exposure at 78K results in oxygen adatoms and small clusters randomly scattered on the surface the NbO surface. Annealing the surface resulted in oxygen clusters residing in the channels between the nanocrystals, where the LDoS is larger. The clusters are regular in size and appearance and fill the channels, resulting in a oxide row structure within the channels. These oxide clusters and the adatoms prior to annealing could not be induced to penetrate the oxide layer using the STM tip. The barrier for oxygen penetration through the NbO terminating layer is high. NbO acts as a protective layer for the underlying Nb bulk. A variety of disordered and ordered sub-monolayer oxide structures are observed when exposing a Cu(111) single crystal to oxygen at various annealing temperatures from 78-850K. The change in the structure of these oxides is monitored over the different preparation conditions. Many oxides co-exist at low temperatures. Increasing the annealing temperature during oxidation reduces the number of distinct oxides. A new ordered oxide structure is observed at 750K. At 850K the ordered oxide observed at 750K has grown from the terrace edges by coalescing the oxide islands which exist on the terraces. The oxide structure has a hexagonal symmetry and a period of 1nm. A second, larger, ordered oxide structure is also observed. This structure has a period of 1.6nm and exhibits a 3-fold symmetry substructure.
APPROVED
Keywords: Surface Science; STM; Copper; Niobium; Molybdenum; Oxide; DFT